Diversity of phenotypic characteristics of White Tailed-Yellow Chicken populations reared under free range system in Phitsanulok Province, Thailand: - - SUPHAWADEE YAEMKONG; TUAN NGUYEN NGOC (Society for Indonesian Biodiversity, 2019)
Abstract. Yaemkong S, Tuan NN. 2019. Diversity of phenotypic characteristics of White Tailed-Yellow Chicken populations reared under free-range system in Phitsanulok Province, Thailand. Biodiversitas 20: 1264-1273.  The objective of this study was to evaluate phenotypic diversity of White tail-yellow chickens in Mueang District, Phitsanulok, Thailand. A total of 200 male chickens from the purposive samples were collected, and then analyzed by using descriptive statistics, correlation and least squares mean for subclasses of each factor. The results showed that the phenotypic of White tail-yellow Chickens had the highest white-yellow beak (60.29%), hin comb (65.50%), golden-yellow neck plumage (95.69%), back plumage (96.17%) and wing plumage (67.94%), white-black long curving tails (70.11%), black back tails (71.14%) and white-yellow shank (59.81%) for qualitative traits. The quantitative traits such as body weight, body height, body length, body width, wing length, shank length, and toes length were 2.78±0.58 kg, 61.95±3.77 cm, 24.93±1.66 cm, 16.62±1.91 cm, 41.85±2.52 cm, 12.72±0.77 cm, and 8.39±0.66 cm, respectively. The highest positive correlation was recorded between neck plumage and back plumage (r=0.70; p<0.01). Moreover, body weight was the highest correlation with wing length (0.58; p<0.01) whereas body length was the highest positive correlation with wing plumage (0.21; p<0.01). However, beak and comb had no significant effect on all traits (p>0.05) except for neck, back and wing plumage, long curving tail, back tail and shank color (p<0.05).